Spiritually grounded character: A latent profile analysis - Ford, Tom; Lipson, Josh; Miller, Lisa (Frontiers in Psychology, 2023)
Introduction The relationship between personal spirituality and character strengths has not been adequately explored. We investigate this relationship in an adult sample via latent profile analysis. Methods Seven-hundred and sixty-three individuals aged 18 to 68years completed a survey of personal spirituality (e.g., Delaney Spirituality Scale), character strengths and virtues (e.g., VIA Inventory), flourishing (i.e., general wellbeing; PERMA Profiler), and various demographic variables (e.g., age, race, sexual orientation, yearly income, education level, religiosity, importance of spirituality and religion, and religious attendance). Latent profile analysis (LPA) was performed to identity profiles of individuals based on their reported levels personal spirituality and character strengths (i.e., VIA virtues). Results A best-fitting model consisting of four distinct, non-overlapping profiles emerged. In every profile, the degree of personal spirituality was consistently associated with strengths of character. Profiles that exhibited high levels of spirituality and character also reported greater levels of flourishing. Furthermore, profiles high in spirituality and character were associated with the observance of formal religion, report of high levels of spiritual and religious importance, and report of frequent attendance of religious services. Discussion These findings suggest that spirituality and character go hand in hand, that higher levels of the conjoint spirituality and character or “spiritually grounded character” correspond to greater wellbeing and may be generated or supported by a formal religious identification, practice, and community.